Talking out of order: task order and retrieval of grammatical gender and phonology in lexical access - Shantz, Kailen; Tanner, Darren (Language, Cognition and Neuroscience, 2017)
Despite early evidence that grammatical gender is retrieved prior to phonology in lexical access, more recent studies demonstrating task effects and non-converging evidence raise doubts about the extent to which this is a general feature of the language production system. We employed the dual-choice go/no-go paradigm with event-related potentials (ERPs) in order to further clarify the time course of retrieval of grammatical gender and phonology. Specifically, we examined how task order influences the relative timing with which these features are retrieved. Results find no clear evidence that grammatical gender is retrieved prior to phonology in a serial manner. Instead, the relative timing with which these features are retrieved is subject to task order, suggesting that prior estimates of lexical access obtained with this paradigm may be confounded by task effects. Overall, our result support parallel access models of feature retrieval during lexical access and suggest that attentional biases may modulate retrieval.